Avifauna diversity in the environmentally sensitive area: Alpha and Beta analyses in Kluang Forest Reserve, southern Peninsular Malaysia - Nur Aina Mahyudin; Nur Athirah Fauzi; Kaviarasu Munian (Biodiversity Data Journal, 2024)
The Permanent Forest Reserve (PFR) is recognised as one of the Environmentally Sensitive Areas (ESAs) in Malaysia`s spatial planning. Incorporating biological factors alongside existing physical attributes is crucial to improve the classification of ESAs. It is important to attain biological diversity information to formulate biological factors, which include vertebrates such as bird communities. Birds are highly sensitive to changes within ecosystems; hence, they play a pivotal role in reflecting the overall ecological condition. Therefore, the study focused on assessing bird species’ richness in the Kluang Forest Reserve (Kluang FR) and compared its bird diversity amongst five PFRs ESAs in southern Peninsular Malaysia. Methods such as mist netting, point count observations and call recording were deployed to calculate the alpha and beta diversity of the bird community. A total of 68 species comprised of 36 families were recorded and the white-rumped shama (Copsychus malabaricus) was the most abundant species in all reserves studied. Principal Coordinates Analysis (PCoA) revealed that the bird diversity in Kluang FR is more similar to bird santuary Panti Forest Reserve compared to the other four forest reserves and indicates that diversification of species richness. However, the absence of published species information in forest reserves poses challenges for comparing bird assemblages amongst different reserves. More extensive studies are needed in Johor and throughout Malaysia to provide data that can effectively assist and support biodiversity conservation and management.